Assessment of Anti-VEGFs in Treating Diabetic Macular Edema in Alfaisal Eye Center, Khartoum, Sudan, 2019 - Ahmedalgabri RHM; Omer T; Zarroug F; Elkhawad AO; Noma M (Dove Medical Press, 2022)
Rayan Hamza Mohammed Ahmedalgabri,1 Tarig Omer,2 Fatima Zarroug,3 Abdullah Omer Elkhawad,1 Mounkaila Noma4 1Department of Pharmacology, University of Medical Science and Technology, Riyadh, Khartoum, Sudan; 2Vitreo Retinal Department, Alfaisal Eye Centre, Riyadh, Khartoum, Sudan; 3Department of Diabetes Education, Ahfad University for Women, Omdurman, Khartoum, Sudan; 4Department of Research Methodology and Biostatistics, University of Medical Science and Technology, Riyadh, Khartoum, SudanCorrespondence: Rayan Hamza Mohammed Ahmedalgabri, Tel +249 918394529, Email rayan2aljabri@gmail.comBackground: Anti-vascular endothelial growth factor (anti-VEGF) medicines have revolutionized DME and DR treatment. Despite the worldwide use of anti-VEGFs, their use remains limited in Sudan. This study aimed to assess the impact of anti-VEGF (ranibizumab and bevacizumab) injections in patients with diabetic macular oedema in Khartoum, Sudan.Methods: An analytical comparative cross-sectional study was implemented in Alfaisal referral eye centre. A Standard questionnaire was used to collect the variables related to the research objectives. Thirty-four patients were recruited; 16 patients under ranibizumab (Lucentis) and 18 under bevacizumab (Avastin). Data were analyzed through SPSS 23, best-corrected visual acuity (BCVA) and central retinal thickness (CRT) measurements were considered as main outcomes to evaluate the treatment effectiveness.Results: Among the 34 participants, 64.7% were males and 35.3% were females, with an average age of 62 years and 13 years of long standing diabetes. A total of 54 eyes received an average of 2.3 injections in an average of 7 months’ period. The mean BCVA before and after treatment for both drugs respectively 0.19 min and 0.21 min was statistically correlated (p = 0.000). For patients under Lucentis, the mean BCVA before and after medication was 0.20 min– 0.24 min and 0.19– 0.19 min for those who used Avastin. The mean central retinal thickness (CRT), before and after treatment for both drugs, was 492.22μm– 422.89μm, respectively, with a significant correlation (p = 0.003). For patients under Lucentis, the mean CRT decreased from 536.30 μm to 425.19 μm; it dropped from 453.16μm to 421.18μm for patients under Avastin. About 79.4% (27/34) of the participants reported that injections were not affordable and 14.7% (5/34) complained from shortage of one dose, regardless of which type of treatment. Glycaemia control, duration of treatment, type and frequency of injections used were found to be the most contributing factors to the effectiveness of anti-VEGF medications.Conclusion: Both anti-VEGF medications are effective in treating DME, Lucentis showed better improvements in BCVA and macular thickness than Avastin. Policymakers in Sudan require urgent alternative strategies to increase access to these medications.Keywords: ranibizumab, bevacizumab, anti-VEGFs, diabetes mellitus, diabetic retinopathy, diabetic macular edema